Obraz miłości małżeńskiej w eklodze Acon Giovanniego Pontana - Raczyńska, Alicja (Collectanea Philologica, 2014)
Acon is one of the six eclogues written by Giovanni Pontano, one of the most remarkable humanists of the Italian Quattrocento. In this work, the author presents an image of conjugal love by the usage of a bucolic context, a model of shepherd love and some myths from Ovid’s Meta- morphoses. He also refers to some facts from his own biography (marriage with Adriana Sassone). The pastoral figures who speak in the eclogue Acon are Petasillus and Saliuncus. They reminisce their master Meliseus (Pontano’s alter ego) who used to sing beautiful songs for his beloved wife Ariadna. The topics of those songs were the period of engagement, the first days of marriage and the pain caused by the separation of the spouses.